2011
DOI: 10.1055/s-0031-1277182
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Lipoic Acid Inhibits Endoplasmic Reticulum Stress-induced Cell Death Through PI3K/Akt Signaling Pathway in FRTL5 Thyroid Cells

Abstract: Alpha-lipoic acid (ALA) has been shown to modulate cell death via PI3K/Akt signal pathway in various cells. In the present study, the effects of ALA on cell death and PI3K/Akt signal pathway linked to cell death-related proteins during endoplasmic reticulum (ER) stress in FRTL5 thyroid cells were evaluated. In FRTL5 thyroid cells, cell viability increased by ALA pretreatment in tunicamycin (TN)-treated cells. When TN was treated, CCAAT/enhancer-binding protein-homologous protein (CHOP) and Bax protein levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…PI3K/Akt signaling plays crucial roles in insulin/IGF-1-mediated cell cycle progression and cell growth in FRTL5 thyroid cells [ 20 ] . We reported that alpha-lipoic acid ameliorates endoplasmic reticulum stress-induced cell death in FRTL5 thyroid cells by activating PI3K/Akt signaling [ 35 ] . PI3K/Akt signaling, which promotes cell survival, is deregulated in cancer cells including ATC cells [ 19 , 21 ] .…”
mentioning
confidence: 93%
“…PI3K/Akt signaling plays crucial roles in insulin/IGF-1-mediated cell cycle progression and cell growth in FRTL5 thyroid cells [ 20 ] . We reported that alpha-lipoic acid ameliorates endoplasmic reticulum stress-induced cell death in FRTL5 thyroid cells by activating PI3K/Akt signaling [ 35 ] . PI3K/Akt signaling, which promotes cell survival, is deregulated in cancer cells including ATC cells [ 19 , 21 ] .…”
mentioning
confidence: 93%
“…CHOP has pivotal roles in regulation of growth and survival through various signal pathways during ER stress [ 22 , 23 ] . Recently, we have reported that alpha-lipoic acid represses cell death in conjunction with CHOP downregulation in FRTL5 thyroid cells exposed to ER stress [ 24 ] . However, whether CHOP aff ects cell survival in ATC cells subjected to SU5416 has not been elucidated.…”
mentioning
confidence: 99%
“…CHOP stimulated by TRB3 leads to cell death through inhibition of PI3K/Akt signal pathway during unfolded protein response in rat pancreatic islets [ 32 ] . Alphalipoic acid ameliorates ER stress-induced cell death by activating PI3K/Akt signal pathway in FRTL5 thyroid cells [ 24 ] . In our study, p21 and phospho-Akt protein levels were diminished in CHOP plasmid transfection before SU5415 treatment.…”
mentioning
confidence: 99%
“…Several pharmacological agents, such as TN, can also induce these effects. TN determines the cell death by disrupting endoplasmic reticulum (ER) integrity . The present study demonstrates that Se supplementation prevents TN‐induced apoptosis and cell death in FRTL5 cells.…”
Section: Discussionmentioning
confidence: 99%